Changes in imatinib plasma trough level during long-term treatment in patients with intermediate- or high-risk gastrointestinal stromal tumors: Relationship between covariates and imatinib plasma trough level - Wu, Xingye; Ge, Yinggang; He, Xuemei; Li, Juan; Zhang, Jun (Frontiers in Surgery, 2023)
Background: Imatinib is the first-line adjuvant treatment for gastrointestinal stromal tumors (GIST). Considering that some studies have suggested that imatinib (IM) plasma trough levels (Cmin) change with time, the aim of this study was to assess the changes in IM Cmin in patients with GIST in a long-term study and to elucidate the relationships between clinicopathological features and IM Cmin. Methods: IM Cmin in 204 patients with intermediate- or high-risk GIST who were taking IM was analyzed. Patient data were grouped according to the duration of medication (A:1-3 months, B:4-6 months, C:7-9 months, D:10-12 months, E: ≤12 months, F:12<–≤36 months, G: >36 months). The correlation between IM Cmin at different time stages and clinicopathological characteristics was assessed. Results: Statistically significant differences were observed between Group A, C, and D (P = 0.049 and 0.01, respectively). In Group E, IM Cmin was correlated with sex (P = 0.049) and age (P = 0.029), and negatively correlated with body weight, height, and body surface area (P = 0.007, 0.002, and 0.001, respectively). In Group F and G, IM Cmin was significantly higher in non-gastric operation patients than in patients with gastrectomy (P = 0.002, 0.036) and was significantly higher in patients with the primary site of others than in the stomach (P < 0.001, = 0.012). In addition, IM Cmin was much higher in patients with mutation sites other than KIT exon 11 in Group F (P = 0.011). Conclusion: This is the first study of IM Cmin during the long-term treatment of patients with intermediate- or high-risk GIST. IM Cmin was the highest for the first three months and then declined, and long-term administration of IM showed a relatively stable plasma trough level. The IM Cmin was correlated with different clinical characteristics at different durations of medication. This means that future "trough level-clinicopathological characteristics" analyses should be time-point-specific. We also need to formulate time-specific medication monitoring plans to improve disease progression due to the occurrence of drug resistance in clinical practice.